2017
DOI: 10.1021/acs.jpclett.7b03097
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Dependence of the Reactivity on the Presence of Steps: Dissociation of D2 on Cu(211)

Abstract: Stepped metal surfaces are usually assumed to exhibit an increased catalytic activity for bond cleavage of small molecules over their flat single-crystal counterparts. We present experimental and theoretical data on the dissociative adsorption of molecular hydrogen on copper that contradicts this notion. We observe hydrogen molecules to be more reactive on the flat Cu(111) than on the stepped Cu(211) surface. We suggest that this exceptional behavior is due to a geometric effect, that is, that bond cleavage on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 53 publications
5
66
1
Order By: Relevance
“…[67][68][69][70][71][72] In this work, we observe systematically higher E 0 (v, J) values (by 30-130 meV) for the fast channel reaction on Cu(211) compared to Cu(111). This is consistent with a recent study by Füchsel et al, 52 who reported molecular beam adsorption measurements and complementary theoretical calculations, showing that the Cu(211) facet is less reactive than Cu(111).…”
Section: The Dependence Of Hydrogen Recombination On Surface Strucsupporting
confidence: 93%
See 2 more Smart Citations
“…[67][68][69][70][71][72] In this work, we observe systematically higher E 0 (v, J) values (by 30-130 meV) for the fast channel reaction on Cu(211) compared to Cu(111). This is consistent with a recent study by Füchsel et al, 52 who reported molecular beam adsorption measurements and complementary theoretical calculations, showing that the Cu(211) facet is less reactive than Cu(111).…”
Section: The Dependence Of Hydrogen Recombination On Surface Strucsupporting
confidence: 93%
“…There have been many studies on the dissociative adsorption of hydrogen on copper. 7,11,13,18,19,23,27,[34][35][36][37][39][40][41][43][44][45][47][48][49][50][51][52]61,65 E 0 (v, J) values from the most directly comparable studies 27,47,51 are shown in Fig. 11 systematically lower, despite the fact that the experimental approach was nominally identical to the present one.…”
Section: A the Fast Channel And Comparison To Prior Experimental Workmentioning
confidence: 48%
See 1 more Smart Citation
“…In method 2, only dynamically relevant points in the barrier region were selected: 300 randomly selected points were taken from QCT calculations, from 10 4 trajectories, a further restriction being 0.7 Å ≤ r ≤ 2.3 Å and 0.9 Å ≤ Z ≤ 3.5 Å. (For more details, we refer the reader to ref ( 43 ).)…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogenation reactions using molecular hydrogen include H 2 adsorption and dissociation. This step is infrequently rate controlling on transition metal surfaces where the dissociation is known to be facile and structure insensitive, with opposing observations often labelled as anomalous . However, the reaction of atomic H with hydrocarbon reactants has been measured to be structure sensitive.…”
Section: Introductionmentioning
confidence: 99%